2006
DOI: 10.1111/j.1467-842x.2006.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and physical activity behaviours among Mäori, Pacific and NZ European children: identifying opportunities for population‐based interventions

Abstract: Objectives:To describe how the prevalences of nutrition and physical activity behaviours vary by ethnicity, while controlling for other socio‐demographic characteristics, and to identify appropriate points of intervention for defined ethnic populations of New Zealand children. Methods:Secondary data analysis of the 2002 National Children's Nutrition Survey. Results:Few ethnic differences were significant for fruit and vegetable consumption and indicators of physical activity. Where ethnic differences in phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…Among adults, 5,6 and observed in this study, compared to Europeans, Pacific Islanders had more servings of eggs, bread and chicken per month and fewer servings of cheese, milk and breakfast cereal per month. Consistent with our findings, the 2002/03 16 and 2006/07 17 New Zealand Health Surveys found that, compared to Europeans, Pacific Islanders were less likely to consume three or more daily servings of vegetables, and the CNS02 found that, compared to NZEO children, a lower percentage of Pacific children ate breakfast cereal daily 3 and Pacific Islanders were more likely to skip breakfast 18 . The Pacific OPIC study showed that in 2005, 58% of Pacific males and 61% of Pacific females consumed at least two daily servings of fruit (unadjusted for energy and age), compared with 68% of European males and 73% of European females 8 .…”
Section: Discussionsupporting
confidence: 88%
“…Among adults, 5,6 and observed in this study, compared to Europeans, Pacific Islanders had more servings of eggs, bread and chicken per month and fewer servings of cheese, milk and breakfast cereal per month. Consistent with our findings, the 2002/03 16 and 2006/07 17 New Zealand Health Surveys found that, compared to Europeans, Pacific Islanders were less likely to consume three or more daily servings of vegetables, and the CNS02 found that, compared to NZEO children, a lower percentage of Pacific children ate breakfast cereal daily 3 and Pacific Islanders were more likely to skip breakfast 18 . The Pacific OPIC study showed that in 2005, 58% of Pacific males and 61% of Pacific females consumed at least two daily servings of fruit (unadjusted for energy and age), compared with 68% of European males and 73% of European females 8 .…”
Section: Discussionsupporting
confidence: 88%
“…One possible explanation for this inconsistency may be reflected in sociocultural factors influencing fruit and vegetable consumption. Previous research in New Zealand has reported higher fruit and vegetable consumption among Pacific children and Māori children, independent of socio-economic position (31) . The lack of association may also reflect recent initiatives targeting obesity prevention in more deprived areas in New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…Model one was adjusted for age only. As sex [21], SES [22] and ethnicity [23] have been found to be associated with food choice, model two included these factors. Model two was repeated using different individual measures of deprivation, including NZDep06, household crowding and car ownership.…”
Section: Methodsmentioning
confidence: 99%